PENGARUH BRAND COMMUNICATION, BRAND TRUST, DAN BRAND SATISFACTION TERHADAP PEMBENTUKAN BRAND LOYALTY PRODUK KOSMETIK BNB BARENBLISS - Banjarnahor, Dinar; Dwiridotjahjono, Jojok (Jurnal Bisnis Indonesia, 2024)
In the current era of globalization and digitalization, advances in technology and information are occurring rapidly. This phenomenon also results in fierce competition in the business world. The only way to maintain the sustainability and competitiveness of a business is to continue to develop company innovation and creativity. The aim of this research is to determine and analyze the influence of brand communication, brand trust and brand satisfaction on the formation of brand loyalty for BnB Barenbliss cosmetic products in the city of Surabaya. The method used in this research uses a quantitative approach and associative research. The sampling technique used in this research is purposive sampling and quota sampling with a sample size of 100 people. The data analysis technique used in this research uses a component-based SEM (structural equation model) research model using PLS (Partial Least Square). The research results For the Brand Communication variable (X1), the p-value obtained is 0.010 < 0.05, so reject Ho. It was concluded that Brand Communication (X1) had a significant effect on Brand Loyalty (Y). If Brand Communication (X1) increases by 1 unit, it will increase Brand Loyalty (Y) by 0.246 units. For the Brand Trust variable (X2), the p-value obtained is 0.000 < 0.05, so reject Ho. It was concluded that Brand Trust (X2) had a significant effect on Brand Loyalty (Y). If Brand Trust (X2) increases by 1 unit, it will increase Brand Loyalty (Y) by 0.341 units. For the Brand Satisfaction variable (X3), the p-value obtained is 0.004 < 0.05, so reject Ho. It was concluded that Brand Satisfaction (X3) had a significant effect on Brand Loyalty (Y). If Brand Satisfaction (X3) increases by 1 unit, it will increase Brand Loyalty (Y) by 0.282 units.Keywords : Brand Communicati,n, Brand Trust, Brand Satisfaction Brand loyalty